Self-Efficacy For Quality of Life For Ischemic Heart Disease Patients: A Systematic Review - Beti Kristinawati; Fahrun Nur Rosyid; Ardhu Rizkiawan; Bintang Viga Handika; Nyofan Wahyu Mardana (Universitas Aisyah Pringsewu, 2023)
Self-Efficacy is a variable that can influence Quality of Life (QoL). Individuals with high self-efficacy will be self-motivated and confident in their ability to engage in healthy lifestyle habits that lower potential risks for ischemic heart disease. This systematic review proposed to assess the research results on how self-efficacy impacts patients' ischemic heart disease (IHD) quality of life. This Systematic Review was conducted on seven articles found in databases online from PubMed, ScienceDirect, Proquest, Scopus, Crossref, Springer, and Google Scholar. Good self-efficacy shows better healthy behavior when compared to respondents with low self-efficacy. Patients with high self-efficacy will adopt healthy behavior patterns, and their quality of life will also be satisfactory. Self-efficacy preservation increases the quality of life of heart disease patients, especially those with conditions that require lengthy therapy, such as ischemic heart disease. The findings contribute to a thorough understanding of the influences of self-efficacy and have implications for enhancing elderly cardiac patients' quality of life.Abstrak: Efikasi Diri merupakan variabel yang dapat mempengaruhi Quality of Life (QoL). Individu dengan efikasi diri yang tinggi akan memiliki motivasi diri dan percaya diri dalam kemampuannya untuk melakukan kebiasaan gaya hidup sehat yang menurunkan potensi risiko penyakit jantung iskemik. Tinjauan sistematis ini diusulkan untuk menilai hasil penelitian tentang bagaimana efikasi diri berdampak pada kualitas hidup pasien penyakit jantung iskemik. Tinjauan Sistematis ini dilakukan pada tujuh artikel yang ditemukan di database online dari PubMed, ScienceDirect, Proquest, Scopus, Crossref, Springer, dan Google Scholar. Self-efficacy yang baik menunjukkan perilaku sehat yang lebih baik jika dibandingkan dengan responden dengan self-efficacy yang rendah. Pasien dengan efikasi diri yang tinggi akan mengadopsi pola perilaku yang sehat, dan kualitas hidupnya juga akan memuaskan. Pelestarian efikasi diri meningkatkan kualitas hidup pasien penyakit jantung, terutama yang memiliki kondisi yang memerlukan terapi jangka panjang, seperti penyakit jantung iskemik. Temuan ini berkontribusi pada pemahaman menyeluruh tentang pengaruh efikasi diri dan memiliki implikasi untuk meningkatkan kualitas hidup pasien jantung lanjut usia.